1967
DOI: 10.1139/f67-111
|View full text |Cite
|
Sign up to set email alerts
|

Rostherne Mere, England, A Further Instance of Guanotrophy

Abstract: Rostherne Mere, Cheshire, England, is a small lake with a maximum depth of about 30 m. It is a normal dimictic eutrophic lake with a diverse benthic fauna, but the sediments of the deepest part of the lake are permanently deoxygenated and are devoid of organisms other than copepods, probably in a dormant state. In the absence of any significant organic pollution from human sources, this condition is attributed to the deposition of faeces from the very large bird population on the lake, both resident and transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1970
1970
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Such enrichment likewise occurs on islands in other archipelagoes: guano increases N and P in soils (Hutchinson 1950;Smith 1976Smith , 1978aBurger et al 1978;Siegfried 1981;Ryan and Watkins 1989;Okazaki et al 1993) and enhances plant growth and primary productivity (Gilham 1977;Burger et al 1978;Smith 1978a;Siegfried 1981;Lindeboom 1984;Ryan and Watkins 1989;Daugherty et al 1990;Myrcha and Tatur 1991;Odasz 1994). Guano also stimulates primary productivity in aquatic systems (e.g., the intertidal: Bosman et al 1986;Bosman and Hockey 1988;Wootton 1991;Beckley and Branch 1992;Loder et al 1996;mangroves: Onuf et al 1977; lotic freshwater systems: Brinkhurst and Walsh 1967;Leentvaar 1967;Manny et al 1994;Kitchell et al, in press). Often, widespread bottom-up eects propagate throughout the food web of communities enriched by allochthonous input (Polis et al 1997b; see below).…”
Section: Discussionmentioning
confidence: 99%
“…Such enrichment likewise occurs on islands in other archipelagoes: guano increases N and P in soils (Hutchinson 1950;Smith 1976Smith , 1978aBurger et al 1978;Siegfried 1981;Ryan and Watkins 1989;Okazaki et al 1993) and enhances plant growth and primary productivity (Gilham 1977;Burger et al 1978;Smith 1978a;Siegfried 1981;Lindeboom 1984;Ryan and Watkins 1989;Daugherty et al 1990;Myrcha and Tatur 1991;Odasz 1994). Guano also stimulates primary productivity in aquatic systems (e.g., the intertidal: Bosman et al 1986;Bosman and Hockey 1988;Wootton 1991;Beckley and Branch 1992;Loder et al 1996;mangroves: Onuf et al 1977; lotic freshwater systems: Brinkhurst and Walsh 1967;Leentvaar 1967;Manny et al 1994;Kitchell et al, in press). Often, widespread bottom-up eects propagate throughout the food web of communities enriched by allochthonous input (Polis et al 1997b; see below).…”
Section: Discussionmentioning
confidence: 99%
“…There, the populations also develop shortly after the onset of thermal and chemical stratification, apparently in association with the development of reducing conditions in the hypolimnion, which are known to have a stimulatory effect upon the physiological activity of the blue-green algae . In Rostherne Mere, oxygen saturation in the hypolimnion falls to less than 10% in summer (Brinkhurst & Walsh, 1967) and the establishment of reducing conditions within one month of the onset of thermal stratifications is indicated by Grimshaw & Hudson's (1970) data concerning the liberation of phosphate and ammonia . Thus, chemical stratification may well have a causal role in the promotion of the annual Microcystis growth in Rostherne Mere .…”
Section: Discussionmentioning
confidence: 99%
“…Microcystis aeruginosa was the most persistent of the two or three major species present . BRINKHURST & WELSH (1967) showed a fairly diverse fauna is present with some correlation between depth and the species present . Seasonal variations were not given however .…”
Section: The Biology Of the Merementioning
confidence: 96%
“…The accumulation of ammonium-nitrogen and phosphorus near the bottom in summer and autumn may be associated with release from the faecal residues which BRINKHURST & WELSH (1967) postulated would account for the absence of benthic fauna there . However release from both faecal and plankton residues is governed by the oxygen content which these authors showed fell to less than 10 saturation at 20 m and 28 m in the summers of 1963and 1964.…”
Section: Nitrogen and Phosphorusmentioning
confidence: 99%